2019
DOI: 10.3928/23258160-20190806-16
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Unilateral Dome-Shaped Macula With Serous Detachment After Treatment of Topical Carbonic Anhydrase Inhibitors

Abstract: Dome-shaped macula (DSM) is a morphological feature outlined through the use of optical coherence tomography and characterized by an inward or anterior deviation of the macula with respect to chorioretinal concavity. Currently, there is no validated therapy for serous retinal detachment secondary to DSM. The authors report a case of childhood unilateral DSM in a hyperopic eye with normal axial length that was complicated with subretinal fluid (SRF). Topical carbonic anhydrase inhibitors may be an acceptable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Different therapies have been proposed for SRF complicating dome-shaped macula, including photodynamic therapy, 242,243 spironolactone, 244 aflibercept, 245 and topical carbonic anhydrase inhibitors. 246 A transient improvement has been observed after surgery for epiretinal membrane. 247 However, all studies were case reports or small series and no comparison with a control group was performed.…”
Section: Dome-shaped Maculamentioning
confidence: 99%
“…Different therapies have been proposed for SRF complicating dome-shaped macula, including photodynamic therapy, 242,243 spironolactone, 244 aflibercept, 245 and topical carbonic anhydrase inhibitors. 246 A transient improvement has been observed after surgery for epiretinal membrane. 247 However, all studies were case reports or small series and no comparison with a control group was performed.…”
Section: Dome-shaped Maculamentioning
confidence: 99%
“…The efficacy of topical monotherapy with CAIs has been reported in several conditions [ 59 ]. The effect of CAIs on retinal edema has been shown in RP with Usher syndrome [ 32 ]; choroideremia [ 60 ]; syndromic retinal dystrophies, such as Alström syndrome [ 61 ]; CME after cataract extraction [ 62 ]; and serous retinal detachment secondary to a dome-shaped macula [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAIs have widely been used as an adjunct for the treatment of macular cysts in various retinal pathologies 10. Chen et al reported a case of unilateral DSM with SRF, which responded to topical therapy with CAIs 3. Mechanism of action of CAIs in the resolution of SRF is not clearly established, though probable theories include restoring normal polarity of retinal pigment epithelium cells, vascular dilatation, accelerated blood flow and thus possible limited remission of scleral compression maculopathy 3 11…”
Section: Discussionmentioning
confidence: 99%
“…Multiple treatment modalities have been advocated in the management of SFD with SRF with variable success. Administration of topical carbonic anhydrase inhibitor (CAI) for DSM with SRF seems to have positive outcomes 3. We report a case of a 5-year-old child diagnosed with myopic DSM with bilateral intraretinal foveal cyst, which responded to topical dorzolamide with improvement in visual acuity.…”
Section: Introductionmentioning
confidence: 99%